การออกแบบตราสินค้าและบรรจุภัณฑ์ผลิตภัณฑ์ท้องถิ่นสู่การต่อยอดสินค้าของฝากประจำจังหวัดและการพัฒนาหลักสูตรชุมชนด้านการจัดการด้านการออกแบบและการเพิ่มช่องทางการตลาด: กรณีศึกษา ชุุมชนหนองน้ำใส จังหวัดสระแก้ว - สุนทรายุทธ รสา (วารสารศิลปกรรมบูรพา, 2021)
This research on local branding and packaging design to the extension as provincial products and community curriculum development on design management and marketing channels expansion : A Case Study of Hnong Namsai Community, Sa Kaeo Province aims to study and research how the local community works by using the idea of design thinking and the way of bringing people together for sustainable developments, designing a local product branding and packaging that can communicate and increase market share of the products. It also led to the design of short-term local community courses on management, branding and packaging design in order to upgrade the products to be as provincial souvenir products. The process will be conducted using semi-structured interviews and questionnaires from a sample group consisting of professors, designers, a leader of local product group and target customers in total of 150 people. For the results of this research and design, the researcher and the team designed the “Nam Sai” logo that can communicate the modern image of the brand of the products - crispy rolls and crispy spirals, which represents the feeling of prosperity, friendliness, locality, healthy and cleanliness. The prototype packaging design is a box that can actually be produced. There are images that communicate fun, bright, compact and convenient. These new packaging designs would help the products in being sold at a higher price than before. It would make more money for the community and also open for the opportunity to be products that tourists can buy as a souvenir as well. In addition, from the creative co-creation process to design the brand and packaging with the villagers of Hnong Nam Sai community. This provides information for designing two short-term community courses, which are a course in management of community product packaging design and a course on increasing marketing channels for community products and branding design. These 2 courses focus on the learning nature of the villagers in order to lead to the development of new ideas for products and more projects on sustainable development of the community in the future.